2014
DOI: 10.1002/2014gl060985
|View full text |Cite
|
Sign up to set email alerts
|

Istanbul's earthquake hot spots: Geodetic constraints on strain accumulation along faults in the Marmara seismic gap

Abstract: During the past century, a series of predominantly westward migrating M > 7 earthquakes broke an~1000 km section of the North Anatolian Fault (NAF). The only major remaining "seismic gap" along the fault is under the Sea of Marmara (Main Marmara Fault (MMF)). We use 20 years of GPS observations to estimate strain accumulation on fault segments in the Marmara Sea seismic gap. We report the first direct observations of strain accumulation on the Princes' Islands segment of the MMF, constraining the slip deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
180
2
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(205 citation statements)
references
References 25 publications
(52 reference statements)
20
180
2
3
Order By: Relevance
“…This is significantly less than longterm slip rates predicted for the NAF in this area [Flerit et al, 2003;Reilinger et al, 2006;Hergert and Heidbach, 2010] or from distant on-land GPS data [Ergintav et al, 2014]. If this slip deficit corresponds to a steady state behavior of the fault, it implies that the NAF is currently accumulating stress at the surface.…”
Section: 1002/2016gl069600mentioning
confidence: 73%
See 2 more Smart Citations
“…This is significantly less than longterm slip rates predicted for the NAF in this area [Flerit et al, 2003;Reilinger et al, 2006;Hergert and Heidbach, 2010] or from distant on-land GPS data [Ergintav et al, 2014]. If this slip deficit corresponds to a steady state behavior of the fault, it implies that the NAF is currently accumulating stress at the surface.…”
Section: 1002/2016gl069600mentioning
confidence: 73%
“…Although Bohnhoff et al [2016] suggest that the maximum expected earthquake in the Istanbul area would probably not exceed a magnitude 7.5, geomechanical models generally predict high strain accumulation along the ISS, sufficient to produce a magnitude 7+ event [Hergert and Heidbach, 2010;Pondard et al, 2007;Armijo et al, 2005;. Conversely, Ergintav et al [2014] proposed that the ISS is aseismically creeping with strain accumulation less than 2 mm/yr, based on GPS data from distant and sparsely distributed land stations. Assessing whether the ISS is locked or aseismically creeping is crucial for estimating its seismic hazard potential and a major challenge using conventional methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that this is a simplification and may not be true everywhere (e.g. Ergintav et al 2014); the coupling coefficient is indeed a crucial parameter, yet it remains rather controversial and very hard to assess homogenously at the scale of the entire continent. The three earthquake source models are characterised by alternative options to calculate and spatially distribute future seismic activity (Fig.…”
Section: Modelling Maximum Magnitudesmentioning
confidence: 99%
“…They concluded that this subsegment might be locked and thus represents a potential nucleation point for an impending Marmara earthquake. This view is also supported by Global Positioning System data (Ergintav et al, 2014).…”
Section: Tectonic Setting and The Gonaf Projectmentioning
confidence: 81%